(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The article examines the social factors that determine the spread of online fraud in the context of the digitalization of modern society. Drawing on domestic and international scholarly literature, victimization survey data, and empirical research, the study analyzes the socio-demographic characteristics of victims, the mechanisms of social trust and its exploitation, and the role of social inequality, digital literacy, and network structures in shaping population vulnerability. Special attention is given to the phenomena of social engineering, the erosion of institutional trust, and the influence of the media environment on victimization. Theoretical explanatory models — routine activity theory, rational choice theory, and the concept of social capital — are analyzed in relation to online fraud. The necessity of socially oriented preventive measures that go beyond technical solutions is substantiated.